Pemanfaatan Media Sosial sebagai Strategi Pengembangan Usaha Pabrik Tahu di Kelurahan Oimbo, Kota Bima - Purnama, Ita; Khairunnisa, Khairunnisa; Oktavia, Fayzha (CV. Devi Tara Innovations, 2025)
. Sardin's tofu factory in Oimbo Village, Bima City, is a micro business that still relies on conventional marketing methods, so it has limited market reach. This study aims to analyze the potential of social media as a promotional strategy to expand the market and increase business competitiveness. The methods used included field observation, training on the use of WhatsApp, Facebook, and Instagram platforms, and qualitative evaluation before and after the intervention. The results showed an increase in digital exposure, with the addition of 85 new followers and an increase in customer interaction through direct messaging. Although it has not had a significant impact on sales, business owners are beginning to understand the importance of digital marketing. The main challenge lies in low digital literacy and technological limitations. In conclusion, continuous assistance and digital strategies that are tailored to the characteristics of business actors can be solutions for developing locally-based MSMEs.